Genetic variations of six orang asli sub-groups in Peninsular Malaysia using autosomal and x-chromosome short tandem repeats (STRs) analysis - Abdullah, Nur Azeelah (2018)
The Orang Asli population represent only about 0.5% of total population of Malaysia. There are 18 sub-groups of Orang Asli that belong to the Semang, Senoi and Proto-Malay. These sub-groups have diverse cultures, traditions, beliefs and languages depending on their ethnicity and location. In this study, a total of 164 blood samples from six Orang Asli sub-groups in Peninsular Malaysia; Semai, Che Wong, Orang Kanaq, Lanoh, Bateq and Kensiu were PCR-type for 15 autosomal STR loci using Identifiler Direct system and 12 X-chromosomal STR loci using Argus X-12 QS system. The allele frequencies and several forensic parameters for STR as well as the genetic structure in the Orang Asli sub-groups were determined. The agreement with Hardy-weinberg Equilibrium (HWE) was confirmed for all loci in Semai and Lanoh sub-groups for autosomal STR results and Che Wong for X-STR results. The combined power of exclusion (CPE) were higher than 0.999. The combined power of discrimination (CPD) also supports the theory that no two individuals would have the same genotype except for identical twins. FGA is the most variable and informative marker for forensic testing of the 15 autosomal STR loci while DXS10146 is the most informative marker for X-STR system of the Orang Asli in Peninsular Malaysia. The Orang Asli sub-groups were plotted closed to each other in the Principal Component Analysis (PCA), suggesting some degree of common ancestry between the subgroups.These findings indicate the uniqueness of the Orang Asli sub-groups and the evidence of their ancient genetic affinities as they represent the first human migration wave out of Africa. The STR and X-STR profile dataset are important for forensic applications and for establishment of the Orang Asli population data in Peninsular Malaysia, which are currently not available for this population.